Impact of Floor- Ground Coupling and Thermal Mass on Seasonal Heating Energy Use in Single - Storey Residential Buildings in a Temperate Climate - Gortych, Marta; Staszczuk, Anna; Kuczyński, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study presents an empirical evaluation of winter heating performance in two full-scale single-storey residential buildings located in a temperate transitional climate in western Poland. The buildings, identical in geometry, layout, and insulation levels, differed in wall thermal mass and subfloor configuration. During the 2018/2019 heating season, the building with medium-weight masonry walls consumed 3.6% less heating energy than its lightweight timber-frame counterpart. In the following season, floor insulation was removed in the masonry building to enable direct ground coupling.
Keywords: winter heating demand; energy performance; ground coupling; subsoil heat; thermal mass; residential buildings; experimental monitoring